Fruit Maturity And Interrelated Effects of Temperature and Container on Longevity of Neem (Azadirachta indica) Seeds - Maithani, G. P.; Bahuguna, V. K.; Rawat, M. M. S.; Sood, O. P. (Indian Forester, 1989)
Fruits of neem were collected at different intervals of maturity. Physiologically mature seeds with maximum germination capacity and longevity were obtained 10 to 12 weeks after flowering (late July to early August) when some of the fruits turned yellow and started falling on the ground. This period coincided with peak green weight, size and a fully grown embryo enclosed in bard fibrous endocarp. Seeds were also stored at room temperature, 15°C and 5°C in sealed polythene bags, perforated polythene bags, perforated cardboard boxes (seeds wrapped in blotters) and over silica gel in desiccators. It was found that sealed containers and low temperature (5°C) are responsible for rapid deterioration of seeds while well aerated containers inhibited deterioration upto certain extent at room temperature and 15°C till 6 months.